Establishing a Successful Extension Program. Issue 8 (2nd August 2018) - Reiter, Mark
Abstract : Starting a new faculty position with an extension appointment this fall? That is exciting! In this month's column, Dr. Reiter shares some tips to help you establish a successful extension program.